Alterations in the limbic/paralimbic cortices of Parkinson's disease patients with hyposmia under resting-state functional MRI by regional homogeneity and functional connectivity analysis. Issue 7 (July 2015) - Su, Meilan; Wang, Song; Fang, Weidong; Zhu, Yingcheng; Li, Rong; Sheng, Ke; Zou, Dezhi; Han, Yu; Wang, Xuefeng; Cheng, Oumei
Abstract Background Hyposmia is a cardinal early symptom of Parkinson's disease (PD), but the pathophysiological mechanisms underlying it remain unclear. Resting-state functional MRI (RS-fMRI) demonstrates spontaneous neuronal activity. We hypothesized that there would be alterations in the olfaction-related regions of the limbic/paralimbic cortices in PD patients with obvious hyposmia by RS-fMRI. Methods We used the "Five Odors for Olfactory Detection Arrays" to test the threshold of olfactory detection (TOD) for 54 PD patients and 22 age-matched controls. Using the mean TOD of the control group, patients were subdivided into two groups: PD with obvious hyposmia (OH-PD, n = 38) and PD with none/less obvious hyposmia (NOH-PD, n = 16). The regional brain activity of all subjects was investigated using RS-fMRI, in combination with regional homogeneity (ReHo) and functional connectivity (FC) analysis. Results There were different ReHo values in the limbic/paralimbic cortices between the OH-PD and NOH-PD groups. ReHo was significantly decreased in OH-PD patients in parts of the traditional olfactory regions (e.g. the amygdala, olfactory gyrus, orbital frontal cortex, parahippocampal gyrus and insula) and some non-traditional olfactory centers (e.g. the rectal gyrus and superior temporal pole), while increased in the left anterior/posterior cingulate cortex. FC analysis revealed decreased functional connectivity within the limbic/paralimbic cortices, especially in regions with reduced ReHo in the OH-PD group. Conclusions PD with hyposmia is related to altered functional activity not only in the traditional olfactory center, but also in some non-traditional olfactory regions of the limbic/paralimbic cortices.